Nation Building and the Construction of Identity: Xenophobia in South Africa - Reilly, Janet E. (Refuge: Canada’s Journal on Refugees, 2001)
This article examines the process of nation building in South Africa and its effect on the rise of xenophobia. It explores the ways in which South Africa’s efforts, since the elections of 1994, to construct a non-racial national identity have led to the exclusion of and the denial of rights to non-citizens. Looking at the history of immigration policy in South Africa, it argues that increased levels of xenophobia among South Africans represent an ever-widening gap between the country’s attempts to restructure itself constitutionally (by altering its laws) and culturally (by changing the people’s perception of what it means to be South African).